Health in Chile’s Recent Constitutional Process: A Qualitative Thematic Analysis of Civil Proposals - CABIESES VALDES, BALTICA BEATRIZ; Sophie Esnouf; Alice Blukacz; Manuel A. Espinoza; Edward Mezones-Holguin; René Leyva (My University, 2022)
(1) Background: In response to the recent political crisis in Chile, the “Agreement for Social Peace and the New Constitution’’ was approved. We aimed to analyze the health-related civil proposals uploaded to the official website for popular participation in the new constitution in Chile. (2) Methods: We carried out a qualitative thematic analysis of 126 health-related valid proposals. Moreover, we analyzed their link to the Health Goals 2030, established by the Ministry of Health of Chile and to the Sustainable Development Goals (SDGs). (3) Results: Sixteen main categories were reached. In all, they were organized into four main areas: (i) the right to health and the establishment of a universal health system; (ii) effective access to selected healthcare services; (iii) improving health outcomes for all and for the relevant subgroups; and (iv) the social determinants of health, health in all the policies, and community health. We found that these four areas were strongly linked to the Health Goals 2030 for Chile and to the SDGs. (4) Conclusions: Despite the fact that the new constitutional proposal was rejected in September 2022, the civil health-related proposals and the areas of health and healthcare were of interest to the citizens as the request showed a strong demand from the population for participation in matters of health, healthcare, and public health.
Keywords: chile; civil participation; democracy; latin america; public health; qualitative research; reform; chile; sustainable development; chile; civil society; constitutional reform; democracy; health policy; local participation; public health; qualitative analysis; chile; democracy; human; public health; qualitative research; review; right to health; social determinants of health; south and central america; sustainable development goal; thematic analysis; chile; sustainable development